Mass-dependence of self-diffusion coefficients in disparate-mass binary fluid mixtures - Binas, I.; Mryglod, I. (Condensed Matter Physics, 2009)
Self-diffusion coefficients of a binary uid mixture with components differing only in their particle masses are studied, in particular the case when mass ratio μ of light and heavy particles tends to zero. These coefficients were calculated within the memory function formalism, using the systematic subsequence of approximations for the relaxation times of velocity autocorrelation function. We obtained a general relation for the self-diffusion coefficients which show polynomial dependence on the mass ratio μ. The obtained expression has a correct Brownian limit. We developed the hierarchy of approximations for the self-diffusion coefficients that tends to an exact result from above and below when the order of approximations increases.